Efektivitas Pembuatan Sistem Informasi Manajemen Perpustakaan SMPN 1 Pantai Labu Berbasis Digital oleh KKN 110 UINSU - Muhammad Dhio Nathama Harahap, Muhammad Dhio Nathama Harahap; Muhamad Alda, Muhamad Alda; Abdul Malid, Abdul Malid; Yardina Fauziah Harahap, Yardina Fauziah Harahap; Faradilla, Faradilla; Fitri Rahmayani, Fitri Rahmayani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This application is built with a user-friendly user interface, so that users i.e. library employees can use it easily. The purpose of developing this system is to improve the operational efficiency of the library and support SMP N 1 Pantai Labu in becoming a public school that focuses on information technology in the future. The methods in this research are field research (field research) and literature research (library research). The results show that the implementation of the library management information system in the SMP N 1 Pantai Labu Library will already be carried out but still has constraints on infrastructure and human resources.